Gingival health status among students in AL-Mustansiria University – College of Dentistry (Mustansiria Dental Journal, 2018)
Gingival health status survey was conducted concerning 19-23 years old studentsin Al- Mustansiria University / college of dentistry.The total sample composed of 150 students (75 males and 75 females).The clinical examination was conducted by using blunt mouth probe, followingthe (GI) described by Silness and Loe (1963).Results of this study have shown that mean of gingivitis decreases with advancingclass level with a high significant difference between all classes due to higherawareness regarding prevention of dental diseases among finished dental students.Results also show that gingivitis among males is higher than that among females forall classes because of having better oral hygiene practices than males.